2017
DOI: 10.1158/1078-0432.ccr-16-1678
|View full text |Cite
|
Sign up to set email alerts
|

Immunization against HIF-1α Inhibits the Growth of Basal Mammary Tumors and Targets Mammary Stem Cells In Vivo

Abstract: Purpose Triple negative breast cancer (TNBC) represents a cancer stem cell enriched phenotype. Hypoxia-inducible factor-1 alpha (HIF-1α) induces the expression of proteins associated with stemness and is highly upregulated in TNBC. We questioned whether HIF-1α was immunogenic and whether vaccination targeting HIF-1α would impact the growth of basal-like mammary tumors in transgenic mice. Experimental Design We evaluated HIF-1α-specific IgG in sera from controls and patients with breast cancer. Class II epito… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
0
26
0
1
Order By: Relevance
“…Therefore, anti-tumor effects of autophagy inhibitors such as CQ is likely to be because of the inhibition of chemotherapy-induced autophagy while anti-tumor effects of autophagy inducers such as rapamycin may result from enhanced cell-intrinsic autophagy [ 9 , 10 ]. It has been reported cancer stem cells play a role in tumor dormancy [ 11 ] and drug resistance [ 12 ], and that immunotherapeutic targeting of breast cancer stem cells inhibits growth of mammary carcinoma [ 13 ]. However, we did not detect the enrichment of CD44+CD24- cancer stem cells following ADR-induced tumor dormancy (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anti-tumor effects of autophagy inhibitors such as CQ is likely to be because of the inhibition of chemotherapy-induced autophagy while anti-tumor effects of autophagy inducers such as rapamycin may result from enhanced cell-intrinsic autophagy [ 9 , 10 ]. It has been reported cancer stem cells play a role in tumor dormancy [ 11 ] and drug resistance [ 12 ], and that immunotherapeutic targeting of breast cancer stem cells inhibits growth of mammary carcinoma [ 13 ]. However, we did not detect the enrichment of CD44+CD24- cancer stem cells following ADR-induced tumor dormancy (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In TNBCs, overexpression of HIF-1α was associated with poor outcome in early stage disease [7] . In a recent study, immunization against HIF-1α inhibited the growth of basal mammary tumors [8] . The same study showed elevation of HIF-1α-specific IgG in TNBC patients.…”
Section: Introductionmentioning
confidence: 98%
“…Hypoxia induces nuclear factor-κB (NF-κB) and HIF-1α successively, leading to the infiltration of M2 macrophages in the tumor microenvironment and tumorigenesis (110). As compared with normal cells, triple-negative breast cancer cells have more HIF-1α-specific IgG, which indicates that HIF-1α is immunogenic (111). Treatment using a HIF-1α vaccine recruits type I T cells to the tumor tissue and effectively inhibits basal-like breast CSCs, which can inhibit tumor metastasis (111).…”
Section: Role Of Hif-1 In Tumor Immunity Of Cscsmentioning
confidence: 99%
“…As compared with normal cells, triple-negative breast cancer cells have more HIF-1α-specific IgG, which indicates that HIF-1α is immunogenic (111). Treatment using a HIF-1α vaccine recruits type I T cells to the tumor tissue and effectively inhibits basal-like breast CSCs, which can inhibit tumor metastasis (111). In order to adapt to chronic hypoxia, CD8 + T cells increase the expression of active HIF-1α and increase their own effector functions (112).…”
Section: Role Of Hif-1 In Tumor Immunity Of Cscsmentioning
confidence: 99%
See 1 more Smart Citation